Cryptocurrency - Ingolf G. A. Pernice; Brett Scott (Internet Policy Review, 2021)
A cryptocurrency system can be understood as a system intended for the issuance of tokens which are intended to be used as a general or limited-purpose medium-of-exchange, and which are accounted for using an often collectively-maintained digital ledger making use of cryptography to replace trust in institutions to varying extents. Against such a backdrop, the singular term cryptocurrency can mean a token, intended to be used as a general or limited-purpose medium-of-exchange, issued via a cryptocurrency system.
Keywords: 300; Cryptocurrency; Bitcoin